An “Argentine” Media in the Corollaries of the Civil War: Galicia and the Textual Borders of "España Republicana"’s Transatlantic Pages - Sánchez, Mariela (Madrygal. Revista de Estudios Gallegos, 2017)
In the framework of transatlantic studies, the present proposal aims to relieve some of the presence of Galicia in España Republicana’s letters, publication of the Spanish Republican Center of Buenos Aires, press organ that housed not only political issues but also cultural in broad terms. Generic anchors and characteristics of a particular medium can be subjected to an analysis based on stories that migrate from some clandestine publication and which become possible nuclei for references to the Civil War and its consequences, dissemination of texts conceived as literary and without possibility of diffusion in Franco’s Spain, and the redefinition of different embodiments of the resistance of writers and writings from and about Galicia. It will be established a selection that focuses on the 40s and 50s, which allows –as studied the convergences but also friction between journalism and literature– to glimpse narrative modes of a largely muted culture, carrying a prominent role in the literary field that figures find, in the pages of the newspaper made in Buenos Aires, a particular resonance. Both prominent personalities as anonymous individuals capable of giving universal and representative samples are taken by a carrier from 1918 until the early 80s of the twentieth century held –despite the distance and the material difficulties that at times endangered their periodicity– the voices, the news and the principles of republicanism, with a prominent place for Galicia.